Numerical simulations of earthquake cycles along the Philippine Fault Zone, Luzon Island, Philippines - Dela Cruz, Laarni S.
The Philippine Fault Zone (PFZ) is a left-lateral strike-slip fault of length about 1200 km from Luzon Island to Mindanao Island. In this study, we simulate earthquake cycles along a portion of the PFZ in Luzon to provide a better understanding on the future occurrence of disastrous earthquakes. We divide the PFZ in Luzon into segments. Records of significant historical and instrumental earthquakes together with results from trenching are used to estimate the recurrence interval on each of these segments. We use the discrete cell model in contrast to the continuous model of [40], because the PFZ in Luzon is quite long and this will require huge computations if a continuous model is used.